Josep Renau: his Importance for Mexican Graphic Design - Vilchis Esquivel, Luz del Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2014)
Josep Renau, studied at the Academy of Fine Arts of San Carlos of Valencia, from his youth actively involved in various social movements, he was a founder of the Union of Writers and Workers Artists of Spain relating to the Association of Revolutionary Writers and Artists of France, for their militancy was in jail in 1932 and 1934 in 1937, during the Civil War, he was director General of Fine Arts, promoted fascism and he was commissioned to organize the Guernica painting from Pablo Picasso, Renau also saved personally the Artistic Treasure from The Prado Museum. Renau's political life was marked by his work as a graphic designer in which he experimented with stylistic influences like photomontage of the Russian Constructivists and the European revolutionary currents. He developed his thinking about responsibility, the designer commitment and the social impact of his work.